Glycosylation changes in the salivary glycoproteins of alcohol-dependent patients: a pilot study. - Kratz, Ewa M.; Waszkiewicz, Napoleon; Kaluza, Anna; Szajda, Slawomir D.; Zalewska-Szajda, Beata; Szulc, Agata; Zwierz, Krzysztof; Ferens-Sieczkowska, Miroslawa (Alcohol & Alcoholism)
AIM: Glycosylation of serum proteins is affected with prolonged heavy drinking, and carbohydrate deficient transferrin (CDT) is well established and highly specific biomarker of sustained alcohol consumption. However, total amount of sialic acid is not the only glycoepitope that may be altered as a result of the disease. This work is focused on glycan structures altered in salivary glycoproteins of alcoholics, indicating the most efficient carriers of such marker glycoepitopes. METHODS: Salivary glycoproteins of 31 alcohol-dependent patients and 21 healthy controls were studied by means of lectin ELISA and lectin blotting with the lectins specific for core and antennary fucose, a2,3-bound sialic acid as well as T and Tn antigens in O-glycans. RESULTS: In direct lectin ELISA, core fucosylation, a2,3 sialylation and expression of T-antigen were significantly lowered in the saliva of alcohol-dependent patients. In lectin blotting ten glycoprotein bands were analyzed. The profile of disease-related alterations was found to be complex, but all six lectins studied here were able to detect altered glycan structures. In some glycoproteins the tendency to correct the glycosylation profile was observed after 7 weeks of abstinence. CONCLUSION: Alterations in the glycosylation profiles in the salivary glycoproteins of alcohol-dependent people were found. Some of salivary glycoproteins, such as a-amylase, clusterin, haptoglobin, heavy and light chains of immunoglobulins, and transferrin, seem to be worthy of detailed glycosylation analysis in the detection of alcohol dependence. Further studies may allow one to estimate if such glycomarkers may also reflect the amount of alcohol intake or the duration of alcohol intake.